Resistance to Blister Rust by Application of Systemic Fungicides on Chir (Pinus roxburghii Sargent) - Shukla, A. N. (Indian Forester, 1996)
Effect of systemic fungicides1ike Bavistin, Bayleton and Topsin-M and Baycorwas studied on the development of stem blisters caused by Cronartium himalayense Bagchee on Pinus roxburghii Sargent for two successive years. Bavistin and Bayleton were found to be very effective at lower and higher concentrations.